Cryptocurrency and Macro-Economic Stability: Impacts and Regulations - Tekat Sukomardojo; Mutia Pamikatsih; Yulian Arpianto; Ani Nuraini; Endang Fatmawati (GoAcademica Research & Publishing, 2023)
This research aims to determine the impact of Cryptocurrency on macroeconomics, especially in terms of inflation, exchange rates, and other relevant aspects. This article also analyzes the various regulatory approaches that governments around the world have implemented to address risks and manage the development of cryptocurrencies. The method used in this research is qualitative with a descriptive-analytic approach. The methods used in this research include collecting data from various sources, including historical cryptocurrency data, macroeconomic data, and cryptocurrency regulatory data. The results of the analysis show that cryptocurrencies can have a significant impact on macroeconomic stability, both positive and negative, depending on factors such as widespread use, price volatility, and role in the global financial system. Additionally, the different regulatory approaches reflect the diversity of global views on cryptocurrencies and the challenges of regulating technological innovation. This article summarizes these findings and underscores the importance of a deep understanding of cryptocurrencies in the era of digital finance.